2009
DOI: 10.1057/rlp.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

E-mail advertising: A study of consumer attitude toward e-mail advertising among Indian users

Abstract: E-mail marketing offers great opportunities for businesses. Marketing activities supported by e-mails allow companies to directly communicate with their consumers without time or location barriers. The topic of advertising via e-mails is of major interest. It addresses consumers with individualized advertising messages via e-mails. This paper discusses its relevance and investigates antecedents of consumer attitudes toward advertising via e-mails. The analysis is based on a consumer survey. For this purpose, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 42 publications
5
29
0
8
Order By: Relevance
“…Irritation refers to "the extent to which the web is messy and irritating to media users" (Eighmey & McCord, 1998). Consumers feel frustrated and chaotic when they receive irritating messages which leads to the negative behavior of individuals that affect attitude and behavioral intention (Haq, 2009). Similar findings have been stated by El-Garhi (2014), that it is easy to control permission based advertising because it is under the control of consumers.…”
Section: Irritationmentioning
confidence: 55%
“…Irritation refers to "the extent to which the web is messy and irritating to media users" (Eighmey & McCord, 1998). Consumers feel frustrated and chaotic when they receive irritating messages which leads to the negative behavior of individuals that affect attitude and behavioral intention (Haq, 2009). Similar findings have been stated by El-Garhi (2014), that it is easy to control permission based advertising because it is under the control of consumers.…”
Section: Irritationmentioning
confidence: 55%
“…Users demand accuracy, timeliness and usefulness in online content (Siau & Shen, 2003), and websites which fulfill informational needs create favorable attitudes (Luo, 2002). Ultimately, the quality of information available on a website directly influences shoppers' perceptions both of the company and of its services, thereby shaping users' attitudes (Haq, 2009).…”
Section: Uses and Gratifications (Uandg) Theorymentioning
confidence: 99%
“…Essentially, when a website utilizes techniques that are offensive, insulting, annoying or overly manipulative, consumers tend to perceive the deployed media as unwanted and irritating (Ducoffe, 1995), leading to negative responses and confusion about the website (Haq, 2009). …”
Section: Uses and Gratifications (Uandg) Theorymentioning
confidence: 99%
“…According to Haq (2009, p. 214), reliability can be the source of the message, not just the advertising message that affects it, and in this context, internet-based ads are less reliable than those communicated through traditional channels. Research by Kelly, Kerr and Drennan (2010) also supports Haq (2009) and shows that if young people do not find social media ads as trustworthy, they get away from them and ignore them. The studies of Brackett and Carr (2001), Zernigah and Sohail (2012), and Tsang, Ho and Liang (2004) have shown that there is a positive relationship between the reliability factor and the attitude toward advertising, that the more the consumers find advertisement messages reliable, the more their attitudes towards those messages get positive.…”
Section: Credibility and Attitude Toward Bumper Advertisingmentioning
confidence: 91%
“…Kelly,Kerr and Drennan (2010),Haq (2009), Zernigah and Sohail (2012) and Tsang,Ho and Liang (2004) in the literature. In addition, a positive and significant relationship was found between the reliability of the bumper advertisements and the advertising value in the study, and H 5b was supported in this context.…”
mentioning
confidence: 98%